1999
DOI: 10.1518/001872099779610950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Head-Slaved and Peripheral Displays on Lane-Keeping Performance and Spatial Orientation

Abstract: To improve the efficiency of images presented in low-cost vehicle simulators, the virtual viewing direction (i.e., the direction in which the image is rendered) can be head-slaved, the display can be surrounded with a less detailed peripheral image, or both. Three simulator experiments were used to evaluate the effect of these techniques on lane-keeping performance and spatial orientation. In Experiment 1, vehicle references or a head-slaved display (HSD) provided feedback on the virtual viewing direction. Veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For example, aircraft identification at 5 nautical miles requires a resolution of 42 pixels/deg (21 cycles/degree) and recognition of a land vehicle at 2 nautical miles requires resolution of about 35 pixels/deg (17.5 cycles/degree) (Turner, 1984). Other types of simulators, e.g., automotive, have shown benefits from using GCMRDs as well (Kappe, Erp, & Korteling, 1999)(see also the Medical simulations and displays section below).…”
Section: Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aircraft identification at 5 nautical miles requires a resolution of 42 pixels/deg (21 cycles/degree) and recognition of a land vehicle at 2 nautical miles requires resolution of about 35 pixels/deg (17.5 cycles/degree) (Turner, 1984). Other types of simulators, e.g., automotive, have shown benefits from using GCMRDs as well (Kappe, Erp, & Korteling, 1999)(see also the Medical simulations and displays section below).…”
Section: Simulatorsmentioning
confidence: 99%
“…Remote driving requires both a wide field of view and enough resolution to be able to discern textures and identify objects. Studies have shown that operators are not comfortable operating an automobile (e.g., jeep) with a 40° field of view system, especially turning corners, but feel more confident with a 120° field of view (Kappe et al, 1999;McGovern, 1993;van Erp & Kappe, 1997). In addition, high-resolution is needed to identify various obstacles, and color can help distinguish such things as asphalt versus dirt roads (McGovern, 1993).…”
Section: Remote Piloting and Teleoperationmentioning
confidence: 99%
“…sFOV Ͼ FOV corresponds to a wide-angle effect, sFOV Ͻ FOV corresponds to a telescope-like view. realistic spatial perception and has a positive influence on motion perception, sense of presence, visual recognition, lane-keeping performance, spatial orientation, spatial updating, navigation, spatial perception, and visuomotor activities (Alfano & Michel, 1990;Arthur, 2000;Hendrix & Barfield, 1996;Kappe, Erp, & Korteling, 1999;Loomis, Klatzky, & Lederman, 1991;Riecke, von der Heyde, & Bülthoff, 2001;Rieser, Hill, Talor, Bradfield, & Rosen, 1992;Ruddle & Jones, 2001). On the other hand, most displays currently have a rather limited FOV (usually below 60 deg.…”
Section: Influence Of Field Of View and External Reference Framementioning
confidence: 99%
“…Different combinations of motion and visuals conditions also resulted in differences in the driver's ability to precisely maneuver the vehicle. We would expect drivers to have less success with precision maneuvers with the HMD due to the lack of peripheral visual stimulation and the interference it has been show to cause in lane tracking (Jamson, 2001;Kappe, van Erp, and Korteling, 1999;DeVries and Padmos, 1997) and understanding subtle self-rotation (Schulte-Pelkum, Riecke, and Von der Heyde, 2003). Drivers tended to drive faster and maneuver more aggressively when using the HMD within cone zones in this study.…”
Section: Discussion Of Results From Experiments #1mentioning
confidence: 99%